Reacción de los mercados accionarios latinoamericanos a los anuncios macroeconómicos (2009)
This paper shows empirical evidence of the effect of macroeconomic announcements (inflation and GDP) on returns, volatility and trading activity for the stock markets of Argentina, Brazil, Chile, Colombia, Mexico and Peru, using daily univariate time series models. Significant contemporaneous effects were found only for Colombia and Peru during inflation announcements and for Chile during GDP announcements. On the other hand, lagged and lead effects from announcements were found in most of the cases, contradicting market efficiency. Besides, inflation announcements are associated to higher volatility whereas those of GDP are to lower volatility for most of the countries.